Fears and Challenges of Acting in the Pandemic Time - Ribut Basuki (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
E-learning has become a popular approach today. However, in drama/theater classes where exercises, rehearsals, and ‘productions’ are done on stage, such an approach was considered impossible, until Covid-19 pandemic strike occurred. The purpose of this paper is to reveal how acting classes dealt with the disruption, the process of selecting and implementing online meeting platforms, the new ‘lesson plan’ to finish the classes, the challenges due to the changes, and evaluation for future practices. The nature of the study is both explanatory and evaluative by action research. Primary data were collected using personal observations and questionnaires. Secondary data were taken from library research pertaining drama/theater, e-learning, online teaching, action research, thematic analysis, etc. By flipping from offline to online learning, acting classes turned out to be manageable. Radical and innovative adaptations should be made to make classes work online, including flipping offline to online meetings, implementing screen/camera knowledge, and using online platforms such as Google Meet, Zoom, WA, and LINE. Moreover, despite the fact that initially online meeting was threatening to the students and the teacher alike, using online meeting platforms for acting classes as blended learning was a good challenge, given appropriate situations and purposes.